2015
DOI: 10.7721/chilyoutenvi.25.3.0062
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Culture on Children's Relationships with Nature

Abstract: This mixed-method study compared 5 to 8 years old children from Canada and Slovakia and their relationship with nature. A total of 52 children participated in this study; more specifically, 26 children from Toronto, Canada and 26 children from Bratislava, Slovakia. The children's relationship with nature was examined through understanding their definition of nature, experiences in and feelings towards nature. Children illustrated a picture of nature and their activities in it. They then participated in semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
(88 reference statements)
1
3
0
Order By: Relevance
“…The drawings made by the children included mainly animals, plants, human‐made structures and other objects. This supports the idea that children may attribute similar meanings to nature (Ahi & Atasoy, 2019; Donnell & Rinkoff, 2015; Stokas et al., 2017). The consistent representation of animals and plants by preadolescents can be explained by the biophilia hypothesis, which suggests that humans have an inherent inclination to focus on living organisms and life‐like processes (Wilson, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…The drawings made by the children included mainly animals, plants, human‐made structures and other objects. This supports the idea that children may attribute similar meanings to nature (Ahi & Atasoy, 2019; Donnell & Rinkoff, 2015; Stokas et al., 2017). The consistent representation of animals and plants by preadolescents can be explained by the biophilia hypothesis, which suggests that humans have an inherent inclination to focus on living organisms and life‐like processes (Wilson, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…Many childhood nature experiences have been linked to a greater likelihood of being involved in ecological and nature-based activities in adulthood (Molinario et al, 2020;Rosa et al, 2018). Yet, the limited existing cross-cultural studies have demonstrated that the extent and the benefits of feeling connected with the natural environment seem to vary in terms of different cultural contexts and in light of different cultural perspectives on nature (Beery et al, 2023;Donell & Rinkoff, 2015). In this respect, the present study explored the relationship between childhood nature activities, adult nature experiences and adult nature connections in a Greek sample.…”
Section: Main Findingsmentioning
confidence: 99%
“…Qualitative data has a richness and depth not often available in quantitative data. For example, in a mixed-methods study conducted by Donnell and Rinkoff (2015), the authors looked at how culture influenced children's perceptions of nature. By examining photographs of nature with children from Canada and Slovakia, drawing and engaging in conversations, the authors could explore how children felt about and experienced nature.…”
Section: Qualitative Interviews With Childrenmentioning
confidence: 99%
“…Drawing is a safe and familiar activity for most children and has been used in previous research to engage children in conversation (Barnikis, 2015;Donnell & Rinkoff, 2015). This was done by asking them to draw the farm or a horse, if they so chose.…”
Section: Interview Processmentioning
confidence: 99%